Corporate Sustainability and Its Relevance for Business: A Bibliometric Approach - Joy, Varghese; Shukla, Akhilesh; Jain, Vijay Kumar (Celebes Scholar pg, 2024)
Previous corporate sustainability research studies have highlighted the relevance and need of sustainability practices that corporations need to undertake. Nevertheless, the scholars have unclarified thoughts on the concept and practice of corporate sustainability. By investigating the theoretical concepts that have arisen in the academic literature and thoroughly assessing the research trends on corporate sustainability by completing a bibliometric analysis, this study intends to document the current literature on corporate sustainability. Data for the bibliometric analysis was identified from the Web of Science database. The researchers used VOSviewer software to visualize the collaboration network among authors, countries, and various institutions. Performance analysis and content mapping have been employed for this study. A total of 1600 research articles published in English were finally selected for detailed analysis. The journal Sustainability has been at the top in publishing research articles on corporate sustainability. The key takeaways from this study will support future scholars in understanding better the conceptual emergence of corporate sustainability and the research trends in corporate sustainability.